Biologia reprodutiva de Kingsleya Ytupora (Decapoda: Brachyura: Pseudothelphusidae), na área do Parque Nacional Serra do Pardo em São Félix do Xingú, Pará, Brasil - RIBEIRO, Maria Karoline Trajano (2022)
Crabs as a whole play an important role in aquatic ecosystems, acting as organic matter breakers and nutrient cyclers, as predators of small invertebrates and vertebrates, as well as prey of different groups of vertebrates. As they act in different links in the food chain and present a complex network of ecological interrelations, knowing the basic aspects of their biology becomes an important tool for monitoring environmental changes and environmental health. The objective of this study was to investigate the reproductive biology of Kingsleya ytupora in a preserved area along the Xingu River. Nine females were captured, stored in a container and sent to the laboratory, where the body measurements of the female were obtained. Then the youngs were removed, counted and measured as the length and width of the carapace, totaling 631 youngs. A linear regression was performed to verify the females effect of CW on the number of youngs, without significantly correlation (r2 = 0.21, p = 0.21). This variation in the number of youngs/female may be related to the maturity of the youngs. This statement is reinforced based on the observations of the females collected and kept individually in buckets with water, where the small crabs left the female abdomen, roamed the environment, returning when there was disturbance.